Calcium signaling mediates five types of cell morphological changes to form neural rosettes - Hříbková, Hana; Grabiec, Marta; Klemová, Dobromila; Slaninová, Iva; Sun, Yuh-Man (Journal of cell science, 2018)
Neural rosette formation is a critical morphogenetic process during neural development, whereby neural stem cells are enclosed in rosette niches to equipoise proliferation and differentiation. How neural rosettes form and provide a regulatory micro-environment remains to be elucidated. We employed the human embryonic stem cell-based neural rosette system to investigate the structural development and function of neural rosettes. Our study shows that neural rosette formation consists of five types of morphological change: intercalation, constriction, polarization, elongation and lumen formation. Ca2+ signaling plays a pivotal role in the five steps by regulating the actions of the cytoskeletal complexes, actin, myosin II and tubulin during intercalation, constriction and elongation. These, in turn, control the polarizing elements, ZO-1, PARD3 and β-catenin during polarization and lumen production for neural rosette formation. We further demonstrate that the dismantlement of neural rosettes, mediated by the destruction of cytoskeletal elements, promotes neurogenesis and astrogenesis prematurely, indicating that an intact rosette structure is essential for orderly neural development.
Keywords: Neurons; lidské embryonální kmenové buňky; apoptóza; Actins; Neural Stem Cells; Cytoskeleton proteins; Cytoskeleton; protein zonula occludens 1; Neural stem cell niche; vápník; tvar buňky; Calcium Signaling; Embryonic stem cells; aktiny; Neural rosette formation; tvorba rozet; Zonula Occludens-1 Protein; myosin typu II; cytoskelet; Cell Lineage; Calcium; Cell Shape; Rosette Formation; buněčný rodokmen; neurogeneze; vápníková signalizace; Humans; Neurogenesis; polarita buněk; Cell Polarity; Myosin Type II; neurony; nervové kmenové buňky; Human Embryonic Stem Cells; Adherens junctions; lidé; Apoptosis